Implementasi Desain Antarmuka Aplikasi MIFIK dengan Pendekatan Multiplatform - Rozzaqy, Hafiz Aditya; Sabariah, Mira Kania; Adrian, Monterico (LOGIC: Jurnal Penelitian Informatika, 2024)
The Faculty of Creative Industries is one of the faculties at Telkom University. Currently, the Faculty of Creative Industries faces issues in information dissemination, including information overload, unclassified information, poorly managed information, excessive use of information media, and difficulty in accessing previously conveyed information. Therefore, the MI-FIK mobile application is being developed to address these challenges. It is expected to have features that facilitate users (lecturers, staff, and students) in obtaining information. This application will be developed using the Flutter framework for easy development of multi-platform mobile applications for Android and iOS. In addition to the mobile application, a web dashboard needs to be developed to manage data and provide accurate information to users. The web dashboard will be developed using the Laravel and JavaScript frameworks. The results of validation testing indicate a 98% compliance for the implementation of the Lecturer/Staff mobile application interface, 97.7% compliance for the Student mobile application interface, 100% compliance for the Admin web dashboard interface, and 100% compliance for the Lecturer/Staff web dashboard interface with the design specifications.